2012
DOI: 10.1371/journal.ppat.1002705
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic Mechanisms Driving Norovirus GII.4 Antigenic Variation

Abstract: Noroviruses are the principal cause of epidemic gastroenteritis worldwide with GII.4 strains accounting for 80% of infections. The major capsid protein of GII.4 strains is evolving rapidly, resulting in new epidemic strains with altered antigenic potentials. To test if antigenic drift may contribute to GII.4 persistence, human memory B cells were immortalized and the resulting human monoclonal antibodies (mAbs) characterized for reactivity to a panel of time-ordered GII.4 virus-like particles (VLPs). Reflectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
380
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(401 citation statements)
references
References 76 publications
19
380
0
Order By: Relevance
“…Most interesting from a biological point of view, and perhaps explaining the observed differences in blocking titers found in this study, the alignment also revealed that the GII.4 NoV strains used in this study have major changes in antigenic epitopes A (amino acids [aa] 294, 296 to 298, 368, and 372), D (aa 393 to 395), and E (aa 407, 412, and 413), as shown in Table 3 (6,7,18,(37)(38)(39). Previous studies have reported epitope A to be highly immunodominant and suggested it was the target of blocking antibodies against early strains (7,38).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Most interesting from a biological point of view, and perhaps explaining the observed differences in blocking titers found in this study, the alignment also revealed that the GII.4 NoV strains used in this study have major changes in antigenic epitopes A (amino acids [aa] 294, 296 to 298, 368, and 372), D (aa 393 to 395), and E (aa 407, 412, and 413), as shown in Table 3 (6,7,18,(37)(38)(39). Previous studies have reported epitope A to be highly immunodominant and suggested it was the target of blocking antibodies against early strains (7,38).…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, there are no amino acid differences between the two strains in site E (Table 3). Short-lived NoV immunity following experimental challenge (15,16), together with an epochal GII.4 evolution pattern, indicates NoV immunity is more complex (17)(18)(19). How long immunity against symptomatic norovirus infection lasts is a question under debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on studies with G2.4 human NoVs it was suggested that antigenic changes facilitating escape from herd immunity may also drive changes in HBGA binding affinities and lead to altered population susceptibility Lindesmith et al, 2012). To model this hypothesis we recently generated neutralization escape mutants by repeatedly subculturing ReCVs under constant serotype-specific polyclonal neutralizing antibody pressure (unpublished data).…”
Section: Neutralization Escape and Hbga Bindingmentioning
confidence: 99%
“…A number of other studies have identified norovirus-specific monoclonal antibodies (mAbs) and single chain variable domains (VHH or Nanobodies) that could block norovirus VLP binding to HBGAs [20,[23][24][25][26][27]. However, most of these antibodies and Nanobodies are genotype specific, which limits their therapeutic potential [28].…”
Section: Introductionmentioning
confidence: 99%